Penggunaan Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar IPA - Dwiana, Ari Aprilia; Handika, Handika (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This research was conducted starting from the fact that there were still many students who had not achieved completeness in science learning outcomes. This class action research was conducted in class VI at SD Pahlawan. The reason for choosing the research location is because the writer is a teacher at SD Pahlawan, and this school has never applied the CTL learning approach to science learning with a total of 9 boys and 9 girls. Data collection techniques used in this study are observation, testing, and documentation techniques. Based on the results of the study it can be concluded that the average teacher activity in cycle I was 65.83% in the sufficient category, increasing to 85.83% in the good category in cycle II. The average student activity in cycle I was 61.34% in the sufficient category, increasing in cycle II to 78.00% in the good category. The increase in the completeness of student learning outcomes was: only 7 (38.88%) completed the pre-cycle, the first cycle increased to 13 (72.22%), and the second cycle increased to 17 (94.44%) who completed. The conclusion of this study is that using the CTL learning approach can improve science learning outcomes on Plant Propagation material, students of class VI SD Pahlawan. Kampar District.